Species and Provenance Trials of Pines in North Bengal - Palit, S. (Indian Forester, 1982)
Trials with fast growing tropical pines, in North Benlal been more than a decade ago. Beging with many, the number gradualy narrowed down to seventeen through a process or elimination. Provenance trials were also taken up with species showing promise initialy. Pinus patula has been found to be a suitable species for both upper and middle hills. Of the different provenances tested, Kenya has been fOund to be superior to others in most of the sites. The other species found promising include, P. kesiya of Philippine origin, P. greggil, P. taeda. P. caribaea (var. bahamensis and hondurensis) and P. elliOttii. Seed bases for species like P. patula, P. kesiya, P. greggii. P. taoda have alredy been established. Nursery methods have more or less been perfected. The constraints regarding supply of seeds for provenance trials still remain. Pinns patula are replace Cryptomeria japonica in various zones.